The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s12520-015-0262-3
|View full text |Cite
|
Sign up to set email alerts
|

Organic residue analysis of experimental, medieval, and post-medieval glazed ceramics

Abstract: Glazed ceramics have not typically been sampled for organic residue analysis because the glaze is not porous; therefore, it is commonly believed that these ceramics cannot absorb substances. Although this is partially true, the aim of this paper is to demonstrate that the glaze may exhibit imperfections due to the production process or the use of ceramics and that these imperfections allow the ceramic matrix to trap residues of the food contained in the vessels. The absorption of organic residues in glazed cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…An illustrative instance is the investigation by Pecci et al (2016) [64], wherein they executed a controlled firing experiment involving glazed vessels and concurrently examined the fatty acid compositions in archaeological pottery. In their experimental firing scenario, they incorporated substances like wine, olive oil, and lentisk oil.…”
Section: Discussionmentioning
confidence: 99%
“…An illustrative instance is the investigation by Pecci et al (2016) [64], wherein they executed a controlled firing experiment involving glazed vessels and concurrently examined the fatty acid compositions in archaeological pottery. In their experimental firing scenario, they incorporated substances like wine, olive oil, and lentisk oil.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of Islamic cooking pots and other domestic containers from 9th-12th century contexts in Sicily has shown that a wide range of animal products, fruits and vegetables were processed, and has yielded important insight into the use of resources in both urban and rural contexts under the same regimes [2]. Previously, residue analysis has been undertaken on pottery from Italian 12th-13th century contexts [3][4][5][6][7], and this approach has also been used to examine the impact of the Norman conquest of England on culinary habits, with particular focus on lesser represented rural populations [8]. However, to date, no study has assessed the use of pottery vessels in post-Islamic contexts in Sicily.…”
Section: Introductionmentioning
confidence: 99%
“…For glazed ceramics, collecting and analyzing residue is a huge challenge as the glaze largely prevents substances from penetrating into the vessel body. Nevertheless, Pecci et al (2016) noted that production flaws or deliberate crackling in certain glazes can allow for organic matter to accumulate even in glazed wares. The present study thus analyzes the residue in crackled wares, more specifically the Ge ware, a type of Chinese greenware or celadon dating to the time of the Song (960-1279), Yuan (1271Yuan ( -1368, Ming (1368-1644), and Qing Dynasties (1644-1912 whose date, origin, and production technique are highly contested.…”
Section: Introductionmentioning
confidence: 99%